Pendidikan Akhlak Anak: Sebuah Tawaran Kajian di Pesantren Studi Kitab Simthu al-Iqyan karya Abdullah bin Ahmad Basaudan - Muhamad Rofingi (IIQ An Nur Yogyakarta, 2022)
This research begins with the author's assumption about the decline of children's morals, which is influenced by the bad currents of globalization and the increase in science and technology which has not become the basis of noble character. Therefore, this study offers a study of children's moral education both at school and in Islamic boarding schools through the thoughts of children's moral education contained in the book Simtu al-'Iqyan Syarah Bugyah al-Ikhwan Wariyah al-sibyan by Abdullah Bin Ahmad Basaudan. This type of research is library research using a hermeneutic approach. Data collection is done by means of documentation. Data analysis uses Content analysis. The results of this study are the approach taken in the simtu al-iqyan book not only cognitively, but also affective which emphasizes the spiritual aspect. So that children are not only smart cognitively but also intuitively